2011
DOI: 10.1002/jat.1698
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induction of sulfotransferases in rat liver and intestine

Abstract: Sulfotransferases (SULTs) are important phase II drug-metabolizing enzymes. SULTs regulation by hormones and other endogenous molecules is relatively well understood, while xenobiotic induction of SULTs is not well studied. Caffeine is one of the most widely consumed psychoactive substances. However, SULTs regulation by caffeine has not been reported. In this report, male and female rats were treated with different oral doses of caffeine (2, 10, 50 mg/kg/day) for 7 days. Western blot and real-time RT-PCR were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It has been reported that the expressions and activities of CYP3A and CYP2D in rat intestine were much lower than those in liver, and SULT2A was deficient in rat intestine (47)(48)(49)(50)(51)(52). In our study, male RIS9 and RIMs were used to investigate the stabilities of veratramine in rat intestinal tract.…”
Section: Intestinal Metabolism Of Veratramine In Intestinal Subcellulmentioning
confidence: 95%
“…It has been reported that the expressions and activities of CYP3A and CYP2D in rat intestine were much lower than those in liver, and SULT2A was deficient in rat intestine (47)(48)(49)(50)(51)(52). In our study, male RIS9 and RIMs were used to investigate the stabilities of veratramine in rat intestinal tract.…”
Section: Intestinal Metabolism Of Veratramine In Intestinal Subcellulmentioning
confidence: 95%
“…Few in vivo studies have examined the effects of dietary components on SULT activity, although caffeine and retinoic acid are possible SULT inducers according to animal studies [ 107 , 108 ] ( Table 6(a) ). Although it is uncertain how their outcomes will translate in vivo , various in vitro studies have indicated the possibility of sulfotransferase inhibition (including competitive inhibition) by wine anthocyanins and flavonols, synthetic food colors (especially red colors), apple and grape juice, catechins including epigallocatechin gallate, quercetin, curcumin, resveratrol, flavonoids (apigenin, chrysin, fisetin, galangin, kaempferol, quercetin, myricetin, naringenin, and naringin), and certain phytoestrogens (daidzein, genistein) [ 3 , 105 ].…”
Section: The Metabolic Pathways Of Detoxificationmentioning
confidence: 99%
“…Although GEE - untreated skn-1 (ok2315) worms also recovered their movements 24-hour post MeHg exposure, pre-treatment with the extract, accelerated the worms recovery. Thus, GEE might decrease MeHg toxicity by increasing antioxidant defenses and/or increasing MeHg excretion, as well as the rate of cellular repair in damaged worms (43, 44). However, GEE did not protect WT worms.…”
Section: Discussionmentioning
confidence: 99%